Investigating the effects of the proliferation of commercial broadcasting on public service broadcasting: the case of Rivers State of Nigeria Broadcasting Corporation - Da-Wariboko, Biobele (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2006)
1992 marked a turning point in Nigeria's broadcasting history as the country formally deregulated her broadcast space. However, it was not until March 2002 that the first commercial radio station was established in Rivers State, a broadcast environment hitherto monopolised by Radio Rivers. The coming of the first independent radio station in Rivers State in March 2002 was followed by the establishment of two other stations in October 2003 and November 2003 respectively. As important as these events in broadcasting in Rivers State are, however, media scholars have argued that in most societies where such change has taken place, public service broadcasters have tampered with their values of being an open space where individuals and groups can come together to be educated, informed, and entertained. This study investigates the extent to which the proliferation of commercial broadcasting outlets has affected Radio Rivers' public service programming and scheduling. Using a combination of qualitative and quantitative research methods, through in-depth interviews and analysis of the mandate and programme schedules, the study established that while Radio Rivers still maintains some public service values, its current programming policy is driven by the need to compete with the commercial broadcasters. This is evidenced in the decrease in the programme space allocated to current affairs and educational programmes on the schedule, (the genre of public service broadcasting), and the increase in attention to advertisements and entertainment programmes, (the genre of commercial broadcasting). The study also confirms the adverse effects of dwindling financial resources as forcing public service radios to compromise on their public service values, as majority of programmes on Radio Rivers current programme schedules are now geared towards attracting advertisers rather than serving the public good and interests. However, the study proved that it is not in all cases that the entry of commercial broadcasters into Rivers State broadcast space has undermined Radio Rivers public service values. Indeed, in leading to the expansion of interactive, news, and the diversification of entertainment programmes spaces on Radio Rivers' programming schedules, the proliferation of commercial broadcasters has yielded some positive effects on Radio Rivers public service values and contribution to the public sphere. The study further highlights the need for some policy reforms at Radio Rivers, such as the introduction of licence fees, increased government funding and loosening government's current control over the station. In addition, there is the need for the edict establishing the station to be amended to reflect the current trends in broadcasting in Rivers State, and above all to reposition Radio Rivers to sustain public good and public interests in its programming.
Keywords: Nigerian Broadcasting Corporation; Broadcasting -- Social aspects -- Nigeria; Mass media -- Social aspects -- Nigeria; Radio Broadcasting -- Social aspects -- Nigeria; Radio in community development; Radio stations -- Nigeria; Radio broadcasting -- Rivers State (Nigeria) -- History